Investigation of the applicability of multi-operational logging machines in Hardwood stands - Horváth Attila László (ACTA SILVATICA ET LIGNARIA HUNGARICA, 2012)
As a result of new developments in technology, harvesters may no longer be confined to softwood forests only. Several studies carried out in black locust, Turkey oak and beech stands have justified the use of these machines in hardwood stands. Evaluating the results of the cost and time analyses we concluded that harvesters are more efficient in several cases compared to traditional felling with chainsaws.